(untitled) (Research, Society and Development, 2022)
Butaphosphan, an organic source of phosphorus, potentiates humoral and cellular immune responses, however, it is still not clear how this occurs. We evaluate the effect of subcutaneous administration of injectable butaphosphan on pro-inflammatory markers and neutrophil activity index of mice challenged with bacterial lipopolysaccharide. Forty-two mice were randomly divided into three groups: Butaphosphan 50 (BUT50, n=14), that received injections of 50 mg/kg of butaphosphan; Butaphosphan 200 (BUT200, n=14), that received injections of 200 mg/kg of butaphosphan and Control (CTL, n=15), that received placebo. Subcutaneous injections were performed twice daily, for eight consecutive days. At the 8th day, half of animals per group were randomly selected to be challenged with bacterial lipopolysaccharide. Two hours after the challenge animals were euthanized, blood and spleen collected to analyze hematological parameters, circulating levels of interleukin 6 (IL-6), 1β (IL-1B) and myeloperoxidase (MPO) tissue activity. Red blood cell count was higher in butaphosphan treated groups. White blood cell count was lower in BUT200/LPS, as consequence of the decreased neutrophil count. Defense cells and IL-6 were elevated in BUT200 group. The use of butaphosphan ameliorate inflammatory markers, both in challenged and not challenged animals.